Some difficulties and strategies in translating Natural Right Feyerabend into Portuguese - Fragelli Hulshof, Monique (Con-Textos Kantianos. International Journal of Philosophy, 2024)
In this paper I intend to present some difficulties in translating Kant's Lectures on Natural Law. I will discuss the peculiar context of translating the manuscript, since it entails notes taken by the student Gottfried Feyerabend and therefore requires the translator to carry out comparison work with other sources. I will present two comparison strategies adopted during translation into Potuguese. The first one is the comparison of the Lectures of Natural Law with Kant's published works, especially with the Groundwork of the Metaphysics of Morals and the Idea of a Universal History. As an example, I will analyze how the ideas of the purposiveness of nature and self-legislation appear in these texts. The second strategy comprises comparing the text of these Lectures with Gottfried Achenwall's Natural Law, a compendium used by Kant as a source for his classes. Through this comparison, it is possible to understand the process of transposing terms from Latin to German, which can contribute to the translation of the German text into Neo-Latin languages, such as Portuguese.